Link scheduling algorithm for industrial wireless networks applied to factory automation. Issue 2 (2020) - Cainelli, Gustavo P.; Feldman, Max; Künzel, Gustavo; Müller, Ivan; Pereira, Carlos E.; Netto, João C.
Abstract: Industrial Wireless Networks are an alternative to wired networks for process automation and factory automation. In this type of network, the network manager is responsible for creating and maintaining the network. One of the tasks of the network manager is the scheduling process. It is desirable that this process be carried out as fast as possible. In factory automation applications, this process becomes even more critical as cycle times are much shorter and the network topology changes more often compared to process automation applications. Therefore, one metric that should be considered when evaluating scheduling algorithms is the expected execution time under certain network conditions. This paper proposes a method that perform a pre-scheduling before the network start operating, in order to reduce the processing time. When new devices join to the network they receive pre-scheduled timeslots, making the search for available slots faster. We also compared the method proposed with scheduling algorithms applied in Industrial Wireless Networks and results show that the technique of pre-scheduling may be appropriate when it is necessary to execute the scheduling process in a fast manner.